Cooperative Farming for Agricultural Produce Export in the South East Region Nigeria: Problems and Prospects - Magnus Moday Ofondu; Onwuka Onwuka Okwara; Obinwanne Kelechi Aruomah; Godswill Agu (Marketing and Business Strategy, 2025)
This study seeks to explore the readiness and willingness of farmers’ cooperative societies to internationalize their offerings by engaging in agricultural produce export, and to identify the factors driving these behavioural intents. Being a quantitative survey involving vibrant farmers’ cooperative societies in the South East region of Nigeria, a structured questionnaire based on the theory of planned behaviour was deployed to generate relevant primary data. The data were analyzed using the SmartPLS structural equation modeling. Findings indicate that financial challenge stands as the major challenge faced by the respondents in internationalization of their offering. Government policies, access to information, management of cooperatives, and subjective norms are the key positive drivers of intention to export. The study provides, practical and theoretical insights